Hyperamylasemia of uncertain significance associated with oral double-balloon enteroscopy - Kopácová, Marcela; Rejchrt, Stanislav; Tachecí, Ilja; Bures, Jan (Gastrointestinal endoscopy, 2007)
BACKGROUND: Double-balloon enterocopy (DBE) is still under evaluation, including its yield and safety aspects. OBJECTIVE: Our purpose was to consider the relationship between DBE and hyperamylasemia. DESIGN: Single-center prospective study. SETTING: Tertiary referral hospital, conducted from March to October 2006. PATIENTS: Thirty-five oral DBEs were carried out in 31 patients (17 men, 14 women). Serum amylase, lipase, C-reactive protein (CRP), and urine amylase were taken before the procedure and 4 and 24 hours after the investigation. Abdominal pain was evaluated with a 3-step scale. MAIN OUTCOME MEASUREMENTS: Only 1 patient had acute pancreatitis after DBE. RESULTS: An elevation of amylase levels after the procedure was found in 51.4% and abdominal pain or nausea or vomiting in 34.3%, but 8.6% of these patients had no hyperamylasemia after DBE. CRP was determined in 25 procedures and the serum lipase level in 14 of these 25 DBEs; elevation of both factors after the procedure was found in 36%. The CRP level was elevated in 60% after the procedure. We found a positive correlation between abdominal pain and serum lipase level (r = 0.72, P = .0032) and negative correlation between abdominal pain and age (r = -0.445, P = .0076). Significant hyperamylasemia seems to be associated with longer duration of DBE (borderline statistically significant, P = .045; 95% CI for difference of means 0.985-82.306). LIMITATIONS: Nonblinded nonrandomized study. CONCLUSIONS: Hyperamylasemia after DBE seems to be rather common, mainly in the longest examinations. Although association of significant hyperamylasemia and acute pancreatitis is possible, it is not obligatory.
Keywords: endoskopy gastrointestinální; pankreatitida; Amylases; Humans; gastrointestinální endoskopie; lidé středního věku; Endoscopes, Gastrointestinal; Female; Aged; dospělí; senioři; lidé; Adult; ženské pohlaví; Male; Middle Aged; amylasy; Aged, 80 and over; senioři nad 80 let; Pancreatitis; mužské pohlaví; prospektivní studie; hyperamylazemie; Endoscopy, Gastrointestinal; Hyperamylasemia; Prospective Studies